2010
DOI: 10.1002/chem.201000597
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Imidazolin‐2‐iminato Molybdenum and Tungsten Benzylidyne Complexes: A New Pathway to Highly Active Alkyne Metathesis Catalysts

Abstract: The reaction of [PhC[triple bond]MBr(3)(dme)] (dme=1,2-dimethoxyethane) with the hexafluoro-tert-butoxides LiX or KX [X=OC(CF(3))(2)Me] afforded the benzylidyne complexes [PhC[triple bond]MX(3)(dme)] (2a: M=W, 2b: M=Mo), which further reacted with the lithium reagent Li(Im(tBu)N), generated with MeLi from 1,3-di-tert-butylimidazolin-2-imine (Im(tBu)NH), to form the imidazolin-2-iminato complexes [PhC[triple bond]MX(2)(Im(tBu)N)] (3a: M=W, 3b: M=Mo). The propylidyne complex [EtC[triple bond]MoX(2)(NIm(tBu))] (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
106
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 103 publications
11
106
0
Order By: Relevance
“…Running the experiments under the same conditions for 1 h afforded the product 5 in virtually quantitative yields (>99%) as a colourless oil after filtration through alumina, exhaustive extraction with diethyl ether and evaporation of the solvent. 1 H and 13 C NMR spectroscopic characterisation indicated in both cases the presence of (spectroscopically) pure 5 [11], see Supporting Information.…”
Section: Alkyne Cross Metathesis (Acm)mentioning
confidence: 99%
See 3 more Smart Citations
“…Running the experiments under the same conditions for 1 h afforded the product 5 in virtually quantitative yields (>99%) as a colourless oil after filtration through alumina, exhaustive extraction with diethyl ether and evaporation of the solvent. 1 H and 13 C NMR spectroscopic characterisation indicated in both cases the presence of (spectroscopically) pure 5 [11], see Supporting Information.…”
Section: Alkyne Cross Metathesis (Acm)mentioning
confidence: 99%
“…Gas chromatographic (GC) measurements were carried out on an SHIMADZU GC-2010 instrument. [Me 3 CC^W {OCMe(CF 3 ) 2 } 3 (DME)] (DME ¼ 1,2-dimethoxyethane) [18], R 3 PNSiMe 3 , R 3 PNH, R 3 PNLi (R ¼ Cy, iPr) [19e21] and the substrates 4 [11] and 6 [22] were prepared according to published procedures. The 1 H and 13 C NMR spectra of the organic metathesis products 5 and 7 are shown as Supporting Information.…”
Section: General Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the variants of the Schrock-type alkylidyne complexes, the imidazolin-2-iminatotungstenneopentylidyne complexes such as 1 and 2 (Scheme 2 a) recently reported by Tamm and co-workers display high catalytic activity in a variety of metathesis reactions at ambient temperature and with low catalyst loadings. [10] The approach of introducing imidazolin-2-imide ligands is based on the strong electrondonating capacity of the imidazolium ring towards the Mo or W center. Theoretical calculations showed that the combination of electron-withdrawing alkoxides, such as hexafluorotert-butoxide, with strongly electron-donating imidazolin-2-imide ligands provides a proper balance between the stability and the electrophilicity of the resulting tungsten alkylidyne complexes of type 1.…”
mentioning
confidence: 99%